Evaluation of diabetic retinopathy screening rates among patients with diabetes: a clinical audit - Kaur, Gurvinder; Agarwal, Aastha (International Journal Of Community Medicine And Public Health, 2025)
Background: Diabetic retinopathy (DR) is the most common microvascular ocular complication of diabetes. The sight threatening DR which can be prevented by timely screening, thus highlighting the importance of DR screening. Methods: A prospective observational study was conducted to evaluate the percentage of patients with diabetes undergoing screening for diabetic retinopathy. The study was done in 2 cycles with time for remedial measures in between the cycles. All the patients who presented to the OPD with known diabetes on treatment, history of pre-existing diabetes, history of gestational diabetes, RBS more than 200 mg/dl and HbA1c more than 6.5% were included in the study. Results: In the first cycle, 78.2% underwent dilated fundus examination. The main reasons for not doing the fundus examination were the patient was within the follow-up period, the patient refused due to various reasons or that the doctor didn’t perform. In the second cycle, the percentage of patients undergone dilated fundus examination rose up to 88.9%. Conclusions: There was a significant lag in the number of patients who undergo dilated fundus examination for dilated retinopathy screening. With the help of educating the healthcare personnel and stressing on the counselling of the patients, the number of screening cases can be improved. But there is a need for continuous efforts for the gap to be fully covered.